Gird‐connected boost inverter for low‐power PV applications with model predictive control. Issue 7 (28th July 2017) - Abdel‐Rahim, Omar; Funato, Hirohito; Haruna, Junnosuke
Abstract : We present a two‐stage inverter with high‐voltage conversion ratio employing modified finite‐set model predictive control (MPC) for utility‐integrated low‐power photovoltaic (PV) applications. The proposed system is suitable for low PV power applications, the calculated efficiency at 150 W input power and 21 times boosting ratio was around 88%. The presented system is a high gain, transformerless, and with less leakage current system. Switched inductor quadratic boost converter composes the first stage of the proposed system, due to its high step‐up ability. It can boost the input voltage up to 30 times. A five‐switch current‐source inverter represents the dc/ac stage. The MPC algorithm are designed to control the system and perform the following tasks, take out the maximum power (MP) from the PV, controls the proposed system to operate at maximum power, step‐up the PV voltage, and introduces low current with low total harmonic distortion (THD) and with unity power factor with the grid voltage. Switching states are selected to reduce the switching losses, but forcing the h‐bridge switches to operate at the fundamental frequency.